SYNTHESIS AND CHARACTERIZATION OF N-SUBSTITUTED MALEISOIMIDES HOMOPOLYMERS AND COPOLYMERS WITH SOME VINYLIC MONOMERS - Al-Azzawi, Ahlam; Yaseen , Mustafa (Iraqi Journal of Science, 2024)
Four N-substituted maleisoimides were prepared via dehydration of the corresponding maleamic acids usingNN,- dicyclohexylcarbodiimide as dehydrating agent. The prepared maleisoimides were introduced in free radical copolymerization with three selected vinylic monomers including acrylonitrile, methylmethacrylate and methylacrylate producing new copolymers having different physical properties. Moreover three maleisoimide homopolymers were prepared via free radical polymerization of N-substituted maleamic acids followed by their dehydration with ethyl chloroformate/Et3N.The new homopolymers and copolymers are of great importance since it contain isoimide ring in their repeating units which rearrange gradually with time and use to the more stable structure of the corresponding imides having thermosetting properties.